E-Recovery Service Quality and E-Loyalty in Indonesian Online Travel Agents - Subandi; Juliater Simarmata; Sarinah Sihombing; T. Herry Rachmatsyah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Indonesia’s travel industry has undergone rapid digital transformation, with online travel agents  emerging as key platforms due to increasing internet penetration, improved digital infrastructure, and rising consumer demand for fast and convenient travel services. This shift has intensified competition, making service quality and effective recovery mechanisms critical for maintaining customer loyalty. This study aims to empirically analyze the effect of e-recovery service quality on e-loyalty, mediated by e-service recovery satisfaction and e-trust among online travel agent customers in Indonesia. Using a descriptive quantitative approach, the study employed SEM-PLS with SmartPLS 3.0 and SPSS 23, involving 150 purposively sampled respondents. The results reveal that e-recovery service quality positively affects e-loyalty, e-service recovery satisfaction, and e-trust. Additionally, e-service recovery satisfaction positively influences e-trust, and e-trust positively impacts e-loyalty. However, e-service recovery satisfaction does not directly affect e-loyalty. In terms of mediation, e-trust partially mediates the relationship between e-recovery service quality and e-loyalty, while e-service recovery satisfaction does not mediate this relationship. Managerially, the study suggests that online travel agent managers should improve compensation policies, such as providing vouchers or points, and enhance service recovery features to ensure quick, user-friendly, and informative problem resolution.